Malaysia’s Natural Treasures: Development of 2D Mobile Learning Application to Unveil the Riches of Malaysia’s Nature - Soh, Pei Yi; Md Fudzee, Mohd Farhan (Applied Information Technology And Computer Science, 2024)
Malaysia contains an abundance of natural treasures and is well-known for its varied ecosystem, distinct biodiversity, and pristine landscapes. There is a lack of existing applications introduced about Malaysia’s nature in Google Play. The existing applications also lack multimedia elements such as audio and videos. Therefore, Malaysia’s Natural Treasures is proposed to develop an interactive mobile learning application for targeted users aged 7 to 12 years old with a gamification approach. The Multimedia Mobile Content Development (MMCD) method is used in this project to develop the proposed application. The usability testing has resulted in an average score of 93.375 which is within the range of “Acceptable” in the Acceptability Ranges Score Scale, graded “A” on the Grade Scale, and rated “Excellent” based on the System Usability Scale (SUS). Therefore, it can be concluded that Malaysia’s Natural Treasures application is suitable for children aged between 7 to 12 years old to know and learn more about Malaysia’s nature from different categories with enjoyment.